Patient-reported outcome measures among breast cancer survivors: A cross-sectional comparison between Malaysia and high-income countries - Rajaram, Nadia; Lim, Zhi Ying; Song, Chin Vern; Kaur, Ranjit; Mohd Taib, Nur Aishah; Muhamad, Mazanah; Ong, Wee Loon; Schouwenburg, Maartje; See, Mee Hoong; Teo, Soo Hwang; Saunders, Christobel; Yip, Cheng Har (Wiley, 2018)
Objectives: Patient-reported outcomes (PROs) in high-income countries (HICs) suggest that physical, emotional, and psychological needs are important in cancer care. To date, there have been few inconsistent descriptions of PROs in low-income and middle-income Asian countries. Using a standard questionnaire developed by the International Consortium for Health Outcomes Measurement (ICHOM), we compared the perceived importance of PROs between patients in Malaysia and those in HICs and between clusters of Malaysian women. Methods: Breast cancer patients were recruited from three Malaysian hospitals between June and November 2017. We compared the proportion of patients who rated PROs as very important (scored 7-9 on a 9-point Likert scale) between Malaysian patients and data collected from patients in HICs via the ICHOM questionnaire development process, using logistic regression. A two-step cluster analysis explored differences in PROs among Malaysian patients. Results: The most important PROs for both cohorts were survival, overall well-being, and physical functioning. Compared with HIC patients (n = 1177), Malaysian patients (n = 969) were less likely to rate emotional (78% vs 90%), cognitive (76% vs 84%), social (72% vs 81%), and sexual (30% vs 56%) functioning as very important outcomes (P < 0.001). Cluster analysis suggests that older, parous, Malaysian women, who were less likely to have received breast reconstructive surgery, were more likely to rate body image and satisfaction with the breast as very important outcomes. Conclusion: Taking into account the differences in PROs by cultural and socioeconomic settings could improve patient expectation of services and refine the assessment of cancer care outcomes. © 2018 John Wiley & Sons, Ltd.